Conceptualization of energy-adapted construction projects in the context of sustainable development, regulatory framework, and digital transformation - Kozak, A.; Sobol, D.; Danilov, S.; Oksenchuk, R.; Sharshun, F. (Ways to Improve Construction Efficiency, 2022)
The study focuses on the conceptualization of energy-adapted construction projects as an important element of sustainable development in the context of modern regulatory requirements and digital transformation in the construction industry. The relevance of the topic is due to the high demands for energy efficiency in buildings, which significantly enhance their competitiveness in the market. Energy-adapted construction projects have become one of the main directions in the strategic planning of the development of the construction industry, where ecological, economic, and social aspects play a crucial role. A key component is the integration of digital technologies, particularly BIM (Building Information Modeling), which enable effective planning, designing, and implementation of energy-efficient projects. The paper examines the interaction between the regulatory framework, state standards, international certifications, and digital platforms for developing construction projects. Special attention is given to analyzing mechanisms for adapting to new conditions, including renewable energy technologies, efficient resource utilization, and energy consumption management. Modern technologies such as solar panels, wind generators, and geothermal systems provide optimization of energy consumption and reduce the reliance of buildings on traditional energy resources. By integrating these technologies and using digital solutions, it is possible to ensure high energy efficiency and environmental sustainability in buildings, which complies with the requirements of contemporary sustainable development. As a result of the research, conclusions were made regarding the impact of digital tools on improving the accuracy and efficiency of construction project management in the context of digital transformation. The implementation of BIM technologies not only improves design but also creates a real opportunity for integrating energy-efficient solutions. In addition, recommendations are provided for implementing energy-adapted solutions at various stages of construction, including the design, construction, and operation stages of buildings, which allows reducing energy costs and improving the efficiency of managerial decisions in the construction industry.